1991
DOI: 10.1128/aem.57.8.2324-2331.1991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for discrimination between strains of Listeria monocytogenes from epidemiological surveys

Abstract: Total cellular DNA from 28 strains of Listeria monocytogenes isolated from food implicated in food-borne illness and from patients with listeriosis was digested with the restriction endonucleases HindIII, HaeIII, and EcoRI. Following agarose gel electrophoresis, the fragments were subjected to Southern blot hybridization with a digoxigenin-labeled cDNA probe transcribed from Escherichia coli 16S and 23S rRNA. The patterns of bands from genomic (DNA fingerprints) and rDNA fingerprints (ribotypes) were used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…A schematic presentation which is often applied in connection with restriction fragment length polymorphism analysis (Tveten et al 1991 ;Lew and Desmarchelier 1992) or ribotyping (Baloga and Harlander 1991;Jacquet et al 1992) is, according to our experience, not possible with RAPD profiles, because of the appearance of weak bands in every RAPD system described so far. The interpretation and comparison is possible only if the strains to be compared are investigated together and loaded adjacent on the same gel and compared directly.…”
Section: Discussionmentioning
confidence: 99%
“…A schematic presentation which is often applied in connection with restriction fragment length polymorphism analysis (Tveten et al 1991 ;Lew and Desmarchelier 1992) or ribotyping (Baloga and Harlander 1991;Jacquet et al 1992) is, according to our experience, not possible with RAPD profiles, because of the appearance of weak bands in every RAPD system described so far. The interpretation and comparison is possible only if the strains to be compared are investigated together and loaded adjacent on the same gel and compared directly.…”
Section: Discussionmentioning
confidence: 99%
“…A valuable tool to study the epidemiology of bacterial diseases is to use repeated DNA sequences as probes to detect restriction fragment length polymorphisms (RFLPs) between bacterial isolates. Although ribosomal RNA gene probes have been used to great effect to generate RFLPs [5][6][7] we sought a novel repeat DNA sequence to provide a greater degree of sensitivity and flexibility to the analysis. Repeated DNA sequences that have commonly been found on bacterial chromosomes, in addition to ribosomal RNA genes [19][20][21], include short, interspersed, repetitive DNA such as repetitive extragenic palindromic (REP) sequences [22], enterobacterial intergenic consensus sequences (ERICs; [23]) and 209 insertion (IS) elements.…”
Section: Discussionmentioning
confidence: 99%
“…A common method of typing bacterial isolates is to compare DNA restriction fragment length polymorphism (RFLP) patterns. These can be generated by hybridising total DNA restriction profiles with DNA 206 probes made from repeated DNA sequences such as ribosomal RNA genes (ribotyping [5][6][7][8]) or insertion sequences [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…With only minor adjustments this technique can be applied to almost any bacterium or strain. In comparative studies with other typing methods it was found to be the most discriminatory test, in particular for typing of L. monocytogenes serotypes 1/2 and 4 [65,158,203,214,217].…”
Section: Restriction Enzyme Analysis (Rea)mentioning
confidence: 97%
“…In general, ribotyping of Listeria isolates involves the restriction enzyme digestion of chromosomal DNA followed by DNA hybridization using an rRNA gene probe. Resulting banding patterns are used to sort Listeria isolates into ribotypes [202] and establish the relatedness of isolates [65,194,204,205]. Ribotyping has been extensively used in epidemiological studies [170,[206][207][208] and automation has allowed the adaptation of this method for routine analysis [209][210][211][212][213][214].…”
Section: Ribotypingmentioning
confidence: 99%